Obesity accelerates cognitive decline by aggravating mitochondrial dysfunction, insulin resistance and synaptic dysfunction under estrogen-deprived conditions - Wasana Pratchayasakul (2018)
© 2015 Elsevier Inc. Chronic consumption of a high-fat diet (HF) causes peripheral insulin resistance, brain insulin resistance, brain mitochondrial dysfunction and cognitive impairment. Estrogen deprivation has also been found to impair cognition. However, the combined effect of both conditions on the brain is unclear. We hypothesized that estrogen deprivation causes brain insulin resistance, brain mitochondrial dysfunction, hippocampal synaptic dysfunction and cognitive impairment, and that consumption of a HF accelerates these impairments in an estrogen-deprived condition. Seventy-two female rats were divided into sham (S) and ovariectomized (O) groups. Rats in each group were further divided into two subgroups to be fed with either a normal diet (ND) or HF for 4, 8 and 12. weeks. At the end of each period, the Morris water maze test was carried out, after which the blood and brain were collect ed for metabolic and brain function analysis. Obesity, peripheral insulin resistance, increased brain oxidative stress and hippocampal synaptic dysfunction were observed at the eighth week in the NDO, HFS and HFO rats. However, these impairments were worse in the HFO rats. Interestingly, brain insulin resistance, brain mitochondrial dysfunction and cognitive impairment developed earlier (week eight) in the HFO rats, whereas these conditions were observed later at week 12 in the NDO and HFS rats. Either estrogen deprivation or HF appears to cause peripheral insulin resistance, increased brain oxidative stress, hippocampal synaptic dysfunction, brain mitochondrial dysfunction and brain insulin resistance, which together can lead to cognitive impairment. A HF accelerates and aggravates these deleterious effects under estrogen-deprived conditions.